Silicon application induced alleviation of aluminum toxicity in xaraés palisadegrass - Baggio, Guilherme [UNESP]; Dupas, Elisângela; Galindo, Fernando Shintate; Megda, Marcio Mahmoud; Pereira, Nathália Cristina Marchiori [UNESP]; Luchetta, Monique Oliveira [UNESP]; Tritapepe, Caio Augusto [UNESP]; da Silva, Marcelo Rinaldi [UNESP]; Jalal, Arshad [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (MDPI, 2021)
Aluminum (Al) toxicity is a major abiotic constraint for agricultural production in acidic soils that needs a sustainable solution to deal with plant tolerance. Silicon (Si) plays important roles in alleviating the harmful effects of Al in plants. The genus Urochloa includes most important grasses and hybrids, and it is currently used as pastures in the tropical regions. Xaraés palisadegrass (Urochloa brizantha cv. Xaraés) is a forage that is relatively tolerant to Al toxicity under field-grown conditions, which might be explained by the great uptake and accumulation of Si. However, studies are needed to access the benefits of Si application to alleviate Al toxicity on Xaraés palisadegrass nutritional status, production, and chemical–bromatological composition. The study was conducted under greenhouse conditions with the effect of five Si concentrations evaluated (0, 0.3, 0.6, 1.2, and 2.4 mM) as well as with nutrient solutions containing 1 mM Al in two sampling dates (two forage cuts). The following evaluations were performed: number of tillers and leaves, shoot biomass, N, P, K, Ca, Mg, S, B, Cu, Fe, Mn, Zn, Al, and Si concentration in leaf tissue, Al and Si concentration in root tissue, neutral detergent fiber (NDF), and acid detergent fiber (ADF) content in Xaraés palisadegrass shoot. Silicon supply affected the relation between Si and Al uptake by increasing root Al concentration in detriment to Al transport to the leaves, thereby alleviating Al toxicity in Xaraés palisadegrass. The concentrations between 1.4 and 1.6 mM Si in solution decreased roots to shoots Al translocation by 259% (from 3.26 to 1.26%), which contributed to a higher number of leaves per plot and led to a greater shoot dry mass without affecting tillering. Xaraés palisadegrass could be considered one of the greatest Si accumulator plants with Si content in leaves above 4.7% of dry mass. In addition, Si supply may benefit nutrient-use efficiency with enhanced plant growth and without compromising the chemical–bromatological content of Xaraés palisadegrass.
Keywords: Al+3 phytotoxicity; Si accumulator plants; Silicon concentrations; Tropical pasture; Urochloa brizantha cv. Xaraés